Advancing transnational assessments of biodiversity drivers in European agriculture with an updated hierarchical crop and agriculture taxonomy (HCAT) - Maja Schneider; David Gackstetter; Jonathan Prexl; Sebastian T. Meyer; Marco Körner (npj Sustainable Agriculture)
Abstract By homogenizing landscapes and reducing natural habitats, modern agriculture plays a significant role in reducing natural species populations worldwide. Despite advances in research, quantifying the impacts of cropping systems on biodiversity remains challenging due to the lack of comprehensive agricultural data. Within the European Union’s (EU) common agricultural policy (CAP), farmers are required to declare cropping arrangements to receive subsidies. The resulting data is collected by each EU member state individually, leading to inconsistent crop taxonomies across the EU, which hinders transnational analyses of agriculture and related impacts. To overcome this barrier, we developed a hierarchical crop and agriculture taxonomy (HCAT), which harmonizes administrative and agricultural data from 16 EU member states. With the release of an upgraded second version of HCAT, we demonstrate, using the example of biodiversity drivers, how a harmonized CAP data set can aid in identifying indicators related to environmental impacts in agricultural landscapes at international scales.